Public health research support through the European structural funds in central and eastern Europe and the Mediterranean - McCarthy Mark (BMC, 2012)
Abstract Background Public health research provides evidence for practice across fields including health care, health promotion and health surveillance. Levels of public health research vary markedly across European Union (EU) countries, and are lowest in the EU's new member states (in Central and Eastern Europe and the Mediterranean). However, these countries now receive most of the EU's Structural Funds, some of which are allocated to research. Methods STEPS, an EU-funded study, sought to assess support for public health research at national and European levels. To identify support through the Structural funds, STEPS drew information from country respondents and internet searches for all twelve EU new member states. Results The EU allocates annually around €7 billion through the Structural Funds for member states' own use on research. These funds can cover infrastructure, academic employment, and direct research grants. The programmes emphasise links to business. Support for health research includes major projects in biosciences, but direct support for public health research was found in only three countries - Cyprus, Latvia and Lithuania. Conclusions Public health research is not prioritised in the EU's Structural Funds programme in comparison with biomedicine. For the research dimension of the new European programme for Structural Funds 2014-2002, ministries of health should propose public health research to strengthen the evidence-base for European public health policy and practice.